Kara Walker - Book of Hours 2020-2021 - Willems, Roger 1969- (ROMA publication, 2022)
Over the course of 202-2021, during the pandemic, Kara Walker has produced series of drawings in the style of a medieval 'Book of Hours'. Enigmatic images appear to traverse a range of time periods, from scenes of biblical and mythological origins, to images of historical violence, to others that suggest more recent political strife. The highly personal nature of these images capture Walker's own response to the intersection of past and present as a way to understand our contemporary political moment. The book comes with a poster